The Validitas dan kepraktisan model pembelajaran Contextual Analysis of Science and Laboratory Problems (CANLABS) pada pembelajaran IPA - Sutarto Sutarto; I Ketut Mahardika; Pramudya Dwi Aristya Putra; Dian Nur Indah Sari; Finda Nor Laela; Aris Singgih Budiarso (Jurnal Penelitian Pendidikan IPA, 2022)
The learning model about Contextual Analysis of Science and Laboratory Problems (CANLABS) is a model that provides opportunities for students to choose several natural events around them that are relevant to the material which is being studied and then explore the phenomenon profoundly in the laboratory. This study aims to analyze the validity and practicality of the CANLABS learning model for science mastery for junior high school students. The trial results of the model development were carried out in the 7th grade of the former Besuki residency (Jember, Bondowoso, Situbondo, and Banyuwangi) with a total of 120 students. The sampling technique was carried out using a purposive sampling area. To measure the validity, use the model validity sheet carried out by experts through the Focus Group Discussion (FGD). Meanwhile, to measure practicality, an observation sheet on the implementation of the learning implementation plan was used by the observer. Based on the analysis, it was found that the content validation and construct validation respectively scored an average of 4.08 and 4.11 with the reliability of the model 96%. Meanwhile, the implementation of the learning implementation plan in preliminary activities, core activities, strengthening activities, closing, and classroom atmosphere with an average score of 3.39 is categorized as very good. Based on the results of the study, it can be concluded that the CANLABS learning model meets the criteria of validity and practicality so that it is suitable in science learning for junior high school students.